Unmet needs in ANCA-associated vasculitis: Physicians’ and patients’ perspectives - Quartuccio, Luca; Treppo, Elena; Urso, Livio; Del Frate, Giulia; Mescia, Federica; Alberici, Federico; Vaglio, Augusto; Emmi, Giacomo (Frontiers in Immunology, 2023)
In recent years, clinical research has increased significantly and therapies for antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis have improved. However, there are still unanswered questions and unmet needs about AAV patients. The purpose of this review is to examine the frontiers of research related to emerging biomarkers eventually predicting relapse, and new therapeutic approaches, not to mention new quality of life assessment tools. Identifying predictors of relapse may help optimize therapeutic strategies, minimize disease recurrence, and reduce treatment-related side effects. In addition, it is important to recognize that patients may suffer long-term consequences of the disease and its treatment, which, although life-saving, is often associated with significant side effects. Our goal, therefore, is to highlight what has been achieved, the pitfalls, and what still needs to be done, comparing the views of physicians and patients.